Ben Jonson's "dotages" : a reconsideration of the late plays - Champion, Larry S. (University of Kentucky Press, 1967)
Although there has been a general revival of interest in Ben Jonson's dramatic work in the past twenty years, little critical effort has been directed to his late plays -- dismissed by John Dryden as the ""dotages"" of an aging mind. Through a close reading of The Devil Is an Ass, The Staple of News, The New Inn, and The Magnetic Lady in light of Jonson's own theories of comedy, author Larry S. Champion demonstrates that they reveal the same precise construction and dramatic control found in his acclaimed masterpieces. Furthermore, these works reflect Jonson's continued emphasis upon reali